Systematic Analysis in the Philosophy of Language - Pavilionis, Rolandas (Problemos, 1974)
The paper presents a critical analysis of the contribution various schools of philosophy and linguistics (logical positivism, ordinary language philosophy, taxonomicbehaviorist, transformational-generative analysis) have made to the philosophy of language. Both the traditional and current approaches are examined in the light of the “continuum conception of meaning” which is being developed by the author and considered by him more adequate with respect to disclosing the function of language in human cognition.